Strengthening Faith Education Through Naqsyabandiyah Tarekat Dhikr Practices - Alya Fadhluna Zamzam; Zulfiana Herni (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Faith education is fundamental in shaping the character and personality of Muslims, serving as a moral foundation and guide in daily life. Specific Background: The Naqsyabandiyah Tarekat, with its long-standing Sufi tradition, emphasizes dhikr (remembrance of Allah) as a core spiritual discipline to deepen faith. At Persulukan Thariqus Sa’adah in Aek Hitetoras Village, structured oral and silent dhikr, guided by mursyid, is central to religious practice. Knowledge Gap: While previous studies explore the moral contributions of Sufi orders, limited research examines how Naqsyabandiyah dhikr methods directly strengthen aqeedah (Islamic creed). Aims: This study investigates the methods, applications, and outcomes of Naqsyabandiyah dhikr in enhancing congregants’ faith. Results: Using a qualitative field approach, findings reveal that consistent dhikr, coupled with sharia adherence, muraqabah (spiritual vigilance), and moral guidance, cultivates tauhid, purifies the soul, and fosters spiritual stability. Congregants report increased closeness to Allah and stronger commitment to Islamic principles. Novelty: The study highlights the integration of Imam al-Ghazali’s Sufi principles with Naqsyabandiyah practices, showing their combined impact on faith formation. Implications: These findings suggest that structured dhikr, rooted in classical Sufi teachings, remains a relevant and effective model for contemporary Islamic faith education and spiritual character building. Highlights: Strengthening aqeedah through structured dhikr. Integration of sharia and spiritual discipline. Relevance of classical Sufi teachings today. Keywords: Faith Education, Naqsyabandiyah Tarekat, Dhikr Practice, Spiritual Development, Imam al-Ghazali